Content/Non-Content Distinction and Protection of Privacy of Electronic Communications Metadata - Bärholm, Sara (fi=Turun yliopisto|en=University of Turku|, 2018)
The data created in connection with communication has historically been divided into two data categories, content and non-content (metadata). This thesis is focused on researching the eroding process of the content / non-content distinction in relation to electronic communications. This thesis expresses an opinion on whether there are still grounds to provide lower level of protection to electronic communications metadata than to content and whether the distinction should disappear entirely. In this thesis, the origins of the distinction as well as the eroding process of it is mainly researched on the basis of case law of the European Court of Human Rights, Court of Justice of the European Union and the Supreme Court of the United States and on the basis of the current and forthcoming European Union law. The distinction between electronic communications content and metadata is significant as it affects to the level of protection granted to the categories of data. Communications content is historically been considered to be in the essence of the right to private and family life and therefore granted more extensive protection than metadata. The distinction was easier to make prior digital communications. However, new communications technology, such as IP-based communications is based on entirely different architecture than the delivery of letters or landline phone calls. The research shows how the developing technology has also changed the nature and impact of processing metadata. Due to these changes the distinction is first of all harder to make and secondly, it no longer is a clear indication of the sensitivity of the data in question. The sensitivity of electronic communications metadata is nowadays comparable to the sensitivity of content. Also, the risks that processing of metadata can cause is recognized in case law and in legislation. Nevertheless, the distinction has not distinguished and communications content and metadata still do not enjoy the same level of protection. From the privacy and confidentiality of communications point of view there are no grounds for granting different level of protection to communications content and metadata.